Pengaruh lama perebusan terhadap daya hambat radikal bebas, viskositas dan sensori sirup secang (Caesalpinia sappan L.) - Sarlina Palimbong; Gelora Mangalik; Alifia Lila Mikasari (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2020)
Sappanwood (Caesalpinia sappan L.) is a plant that can be used as a traditional medicine to treat tuberculosis, diarrhea, dysentery, skin infections, anemia, and several other diseases. Sappanwood containing brazilin as the main compound which has antioxidant properties. The main compound of sappanwood can be presented in the form of products such as syrup. The syrup is practical and makes it easy for consumers to get the functional properties of brazilin. The process of making syrup used boiling method. The purpose of this study was to see the effect of boiling time on the inhibition of free radicals, viscosity and sensory sappanwood syrup. Sappanwood extraction with maceration method using water. The making of sappadwood syrup used additional material cinnamon, lemongrass, ginger, and clove boiled with water and sugar until it thickens. Syrup boiling time is 60, 90, and 120 minutes at a temperature of 60-70°C with three replications. Then the syrup is tested for inhibition using the DPPH method, viscosity, and sensory. Data analysis techniques using Microsoft Excel software. The results showed that boiling time resulted in a decrease in inhibition of free radicals, where the initial inhibition was 56,644% to 28,803%, 22,776% and 29,593%. The viscosity of the sappanwood syrup increases with the length of boiling time. Based on sensory tests, the level of panelist preference is influenced by the length of boiling. Panelists prefer syrup that is boiled for 90 minutes for the parameters of taste, color, and thickness while for the scent panelists like syrup that was boiled for 120 minutes.